Writing Material Analysis of Office Administration English Textbook: Strengths And Weaknesses - Iga Yolanda (English Language and Literature International Conference (ELLiC) Proceedings, 2018)
Textbook is seen as language input for language learners to achieve the learning objectives. However, not all of the materials in the textbook are suitable with the learners‟ need. Thus, textbook analysis is needed to evaluate the quality of the textbook to be able to fulfill the learners‟ need. The aim of this study is to find out the strengths and weaknesses of the writing materials which are used by office administration students in SMK. This study used descriptive qualitative design with book analysis and interview method to collect the data. The data sources of this study were English Textbook entitled “Get Along with English for Vocational School Grade XI Elementary Level” and the English teachers. The findings show that the textbook has several strengths and weaknesses. The textbook contains the explanation about grammar with a wide range of activities. It also provides the glossary at the end of every chapter. Unfortunately, the contents are too general and not specialized for office administration study program. It also does not focus on writing activities and has no explanation about the use of punctuation.